RESPON PAKLOBUTRAZOL TERHADAP PERTUMBUHAN DAN HASIL PADI LOKAL WESEL - Runtunuwu, Semuel D.; Sumampouw, D. M.F.; Tumewu, P.; Mamarimbing, R.; Rengkung, R. M.N. (EUGENIA, 2016)
ABSTRACTÂ Response of rice to paclobutrazol (PBZ) depends on plant variety. This experiment were done to know the influence of PBZ to growth and yield of local rice Wesel using randomized block design (RBD). The treatment consist of four dosages of PBZ with four replications. The results showed PBZ treatmant enhance of grain yield per plant, number of productive tillers (NPT),Â  weight of 1.000 grains, crop growth rate (CGR), and leaf chlorophyll content.Keywords: Paclobutrazol (PBZ), crop growth rate (CGR), chlorophyll, yield, local rice